EFFECT OF METFORMIN IN REDUCTION OF ANTI-PSYCHOTIC MEDICATION INDUCED WEIGHT GAIN IN SCHIZOPHRENIA - Khan, Muhammad Firaz; Haq, Sami Ul; Murad, Khadija; Nazar, Zahid (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine the effect of Metformin in reducing Olanzapine induced weight gain in people with Schizophrenia. Methodology: This randomized controlled trial was conducted on 138 patients at Psychiatry unit, Lady Reading Hospital Peshawar, from August 2016 to February 2017. Patients diagnosed with schizophrenia by consultant psychiatrists in both outpatient and inpatient were included. They were randomly allocated to two groups by lottery method. Intervention group received Olanzapine plus Metformin while control group received Olanzapine plus placebo. Weight was measured in kilograms in all patients at baseline and follow-up at 12 weeks. Results: Number of patients included were 138 (69 in each group) with age range of 17 to 60 years. Mean age of participants for group A was 29 years with SD ± 2.68 while for group B it was 30 years with SD ± 2.91. Group A had 60% male and 40% female patients whereas in group B, 62% patients were male and 38% patients were female. In group A mean decrease in weight was 2.62 kg (SD ± 3.13) while in Group B mean decrease was 1.57 Kg (SD ± 2.83). Conclusion: Mean decrease in weight from baseline in Olanzapine plus Metformin group was more than the Olanzapine plus placebo group.